2013
DOI: 10.1002/cncr.28382
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of multitrial data investigating quality of life and symptoms as prognostic factors for survival in different tumor sites

Abstract: BACKGROUND:The objective of this study was to examine the prognostic value of baseline health-related quality of life (HRQOL) for survival with regard to different cancer sites using 1 standardized and validated patient self-assessment tool. METHODS: In total, 11 different cancer sites pooled from 30 European Organization for Research and Treatment of Cancer (EORTC) randomized controlled trials were selected for this study. For each cancer site, univariate and multivariate Cox proportional hazards modeling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 47 publications
9
132
3
5
Order By: Relevance
“…A follow-up analysis from this cohort showed the predictive value of physical functioning for survival for most cancer sites, in addition to other QOL domains (for example, physical functioning, emotional functioning, global health status and nausea and vomiting were predictive in breast cancer patients, and physical functioning and pain were predictive in lung cancer patients). 29 We had hypothesized that baseline QOL would mediate survival post allogeneic HCT and we found that PWB was independently significantly associated with overall survival. PWB is a measure of patient-reported symptoms including energy, nausea, and side effects of 'feeling ill. ' We thus hypothesized that QOL would primarily mediate survival through its association with NRM.…”
Section: Discussionmentioning
confidence: 75%
“…A follow-up analysis from this cohort showed the predictive value of physical functioning for survival for most cancer sites, in addition to other QOL domains (for example, physical functioning, emotional functioning, global health status and nausea and vomiting were predictive in breast cancer patients, and physical functioning and pain were predictive in lung cancer patients). 29 We had hypothesized that baseline QOL would mediate survival post allogeneic HCT and we found that PWB was independently significantly associated with overall survival. PWB is a measure of patient-reported symptoms including energy, nausea, and side effects of 'feeling ill. ' We thus hypothesized that QOL would primarily mediate survival through its association with NRM.…”
Section: Discussionmentioning
confidence: 75%
“…The survival and quality of life of many patients with cancer are negatively affected by treatment-induced side effects, two of which are nausea and vomiting (1)(2)(3). Chemotherapy is thought to induce nausea and vomiting by triggering the release of neurotransmitters from cells lining the gastrointestinal (GI) tract.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, other patient-reported symptoms have been more extensively studied and their importance as independent prognostic factors in various cancers, including advanced colorectal cancer, has been confirmed 1,[17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%